Complicaciones septicas en pacientes con enfermedades crónicas en el servicio de emergencia del Hospital Regional de Loreto, entre enero 2020 - diciembre 2022 - Vela Ly, Luis Martín (2025)
GENERAL OBJECTIVE: To evaluate the presence and complications of sepsis in patients with chronic diseases at the Regional Hospital of Loreto between January 20 20 - December 2022. MATERIALS AND METHODS: A quantitative study will be conducted. By examining the event as it occurs, this research is distinguished by the researcher's participation in an observational study. By attempting to link two research variables, the scope is analytical. Since the research variables will only be measured once, it is cross-sectional. Data collection is planned retrospectively. All patients presenting to the emergency department of the Regional Hospital of Loreto with a diagnosis of sepsis will be included in the research population, along with a sample of 350 patients diagnosed with sepsis. Systematic random sampling will be used to select medical records. CONCLUSIONS: Eleven million people die from sepsis each year, and vulnerable groups account for approximately 85% of sepsis cases and associated mortality. Obesity, type 2 diabetes, high blood pressure, and other chronic diseases have been linked to higher mortality rates among patients with sepsis.